2020
DOI: 10.3390/sym12030441
|View full text |Cite
|
Sign up to set email alerts
|

Material Symmetries in Homogenized Hexagonal-Shaped Composites as Cosserat Continua

Abstract: In this work, material symmetries in homogenized composites are analyzed. Composite materials are described as materials made of rigid particles and elastic interfaces. Rigid particles of arbitrary hexagonal shape are considered and their geometry described by a limited set of parameters. The purpose of this study is to analyze different geometrical configurations of the assemblies corresponding to various material symmetries such as orthotetragonal, auxetic and chiral. The problem is investigated through a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…For homogenization of discrete structures possessing strong anisotropy as orthotropic textures, a full micropolar model is needed (for more discussion on the topic see [ 31 , 54 , 75 ]). In this case, the non-symmetries (skew-symmetries) of the strain and stress tensors play a relevant role.…”
Section: Equivalent Continuum Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For homogenization of discrete structures possessing strong anisotropy as orthotropic textures, a full micropolar model is needed (for more discussion on the topic see [ 31 , 54 , 75 ]). In this case, the non-symmetries (skew-symmetries) of the strain and stress tensors play a relevant role.…”
Section: Equivalent Continuum Modelsmentioning
confidence: 99%
“…Classical theory of elasticity (Cauchy of Grade 1), on the other hand, fails to accurately homogenize the discrete nature into a continuum medium for a structure having comparable internal and external lengths [ 22 , 23 ]. This drawback can be overcome by means of non-classical (non-local) continuum theories which simultaneously utilize field description at coarse level, and preserve the memory of material’s underlying structure at fine level through internal scale parameters [ 24 , 25 , 26 , 27 , 28 , 29 ] that can refer to different physical features ranging from nano order (e.g., distance between atoms in a nanoscopic structure) up to meso/macro orders (size of particle/grain in a composite medium) as demonstrated in different studies [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…These models, which present additional degrees of freedom, can be classified as 'implicit/ weak' non-local models [11,28,29]. The literature shows that they have been satisfactorily applied to various composites [10,13,[30][31][32][33][34][35][36][37][38][39][40]. Different works moreover, [41][42][43][44][45][46] proposed multiscale computational homogenization with 'explicit' non-local or higher order deformation gradient theories in composite materials [47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…In general, different nonlocal theoretical frameworks can be developed. Examples of nonlocal approaches that should be mentioned for completeness purposes are the strain and stress gradient theories [ 58 , 59 , 60 ], the modified couple stress theory [ 61 , 62 , 63 , 64 ], and the ones based on micropolar formulations [ 65 , 66 , 67 ]. A comprehensive literature review concerning nonlocal elasticity can be found in the paper by Zhao et al [ 68 ] for completeness purposes.…”
Section: Introductionmentioning
confidence: 99%